Clinical experiences in fungal keratitis caused by Acremonium - Kim SJ (Dove Medical Press, 2014)
Seong-Jae Kim,1,2 Yong-Wun Cho,1 Seong-Wook Seo,1,2 Sun-Joo Kim,2,3 Ji-Myong Yoo1,21Department of Ophthalmology, 2Gyeongsang Institute of Health Science, 3Department of Laboratory Medicine, Gyeongsang National University, College of Medicine, Jinju, KoreaPurpose: To report the predisposing risk factors, clinical presentation, management, and therapeutic outcomes of fungal keratitis caused by Acremonium.Methods: This is a retrospective study of cases with Acremonium fungal keratitis that presented to our tertiary referral center between January 2006 and August 2012. Patient demographic and clinical details were determined and reported.Results: Five cases of fungal keratitis from Acremonium species were identified in five patients (three males, two females). The mean age of the patients was of 73.4±5.46 years, with a mean follow-up time of 124±72 days. All patients had a history of corneal trauma with vegetable matter. Four cases were unresponsive to initial treatment (0.2% fluconazole, 0.15% amphotericin B) and required topical 5% natamycin, and, in two out of five cases, topical 1% voriconazole.Conclusion: The most common risk factors for Acremonium fungal keratitis was ocular trauma. When a corneal lesion is found to be unresponsive to the initial treatment, we should consider adding or substituting topical natamycin or voriconazole for treatment.Keywords: Acremonium, fungal keratitis, natamycin, prognosis, voriconazole